Emerging perspectives on managing organizational justice - Steiner, Dirk; Skarlicki, Daniel; Gilliland, Stephen (Research in social issues in management ;, 2002)
This book is divided into three parts: integrating the non-work context into theories of organizational justice; non-work reactions to injustice; and commentary.